2015
DOI: 10.1155/2015/103686
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Diagnostic Approach to Sleep Apnea in Hemodialysis Patients: A Population Study

Abstract: Background. Previous observations found a high prevalence of obstructive sleep apnea (OSA) in the hemodialysis population, but the best diagnostic approach remains undefined. We assessed OSA prevalence and performance of available screening tools to propose a specific diagnostic algorithm. Methods. 104 patients from 6 Swiss hemodialysis centers underwent polygraphy and completed 3 OSA screening scores: STOP-BANG, Berlin's Questionnaire, and Adjusted Neck Circumference. The OSA predictors were identified on a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 42 publications
2
14
0
Order By: Relevance
“…The screening phase of our study represents the largest cohort of ESKD patients on a kidney transplant waiting list studied by full PSG (n = 196). It shows a remarkably high prevalence of moderate to severe SA in this population (44.9%), consistent with the figures obtained in patients on dialysis . Our data add new insights to the existing evidence from previous observational and interventional studies, which identified fluid overload as a population‐specific pathophysiological mechanism of SA in ESKD patients, promoting SA through the so‐called “overnight rostral fluid shift.” Accordingly, the negative fluid balance obtained by hemodialysis has been shown to decrease the severity of SA in overhydrated ESKD patients, even in the absence of any change of the uremic and acid‐base status .…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The screening phase of our study represents the largest cohort of ESKD patients on a kidney transplant waiting list studied by full PSG (n = 196). It shows a remarkably high prevalence of moderate to severe SA in this population (44.9%), consistent with the figures obtained in patients on dialysis . Our data add new insights to the existing evidence from previous observational and interventional studies, which identified fluid overload as a population‐specific pathophysiological mechanism of SA in ESKD patients, promoting SA through the so‐called “overnight rostral fluid shift.” Accordingly, the negative fluid balance obtained by hemodialysis has been shown to decrease the severity of SA in overhydrated ESKD patients, even in the absence of any change of the uremic and acid‐base status .…”
Section: Discussionsupporting
confidence: 89%
“…Kidney transplantation (Tx) restores kidney function and corrects the hydration status of ESKD patients. A previous polysomnographic study reported a SA prevalence of 22% in kidney Tx recipients, which is similar to the prevalence of SA in the general population and lower than that in ESKD patients on hemodialysis . This observation indirectly suggests a beneficial effect of kidney Tx on SA severity.…”
Section: Introductionsupporting
confidence: 69%
See 2 more Smart Citations
“…The relationship between OSA and CKD has been the object of great interest. In patients with end‐stage renal disease (Forni Ogna et al ., ; Kuhlmann et al ., ; Unruh et al ., ), as well as with less severe forms of CKD (Nicholl et al ., ; Sakaguchi et al ., ), a high prevalence of OSA has been reported. Among other mechanisms, renal failure could promote OSA by causing increased chemoresponsiveness or increased fluid retention and upper airway collapsibility through rostral fluid shift when assuming a recumbent position (Abuyassin et al ., ; Lyons et al ., ).…”
Section: Discussionmentioning
confidence: 99%